Pile design practice in southern Africa Part 2: Implicit reliability of existing practice - J V Retief; M Dithinde (Journal of the South African Institution of Civil Engineers, 2013)
Limit state design has become the basis of geotechnical design codes worldwide. With the semi-probabilistic limit state design approach, load and resistance factors of (deterministic) design functions are calibrated on the basis of reliability theory. The calibration is done to obtain procedures that will ensure that a target level of reliability is exceeded under the design conditions within the scope of the design function. This is conventionally expressed in terms of the reliability index (β), which is related to the probability of failure (Pf). Acceptable existing design practice is an important source of information on appropriate levels of reliability. This paper uses the results from a pile load test database to evaluate the reliability levels implied in the current South African pile design approach. The results of the analysis indicate that the reliability index values for ultimate limit state failure of single piles implicit to present design practice vary with the pile class. However, the influence of the probability model applied is more significant. Based on conventional and standardised procedures for reliability analysis, a representative implicit reliability index value βI Rep 3.5 is obtained, corresponding to a probability of failure Pf = 2.10-4. The values for various sets of pile conditions range from βI = 3.1 (Pf = 1.10-3) to βI = 4.3 (Pf = 1.10-5). This compares well with target levels of reliability for structural and geotechnical performance of βT = 3.0 as set in SANS 10160-1:2011 Part 1 Basis of structural design. These indicative results provide a useful reference base to establish the reliability of existing and therefore acceptable South African pile design practice. It could also be interpreted as indicative of geotechnical design practice in general. The standard SANS 10160-5:2011 Part 5 Basis for geotechnical design and actions provides the framework for future calibration investigations.